The Role of IL-13, IL-15 and Granulysin in the Pathogenesis of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis - Sadek, Michael; Iqbal, Omer; Siddiqui, Fakiha; Till, Sean; Mazariegos, Melissa; Campbell, Edward; Mudaliar, Kumaran; Speiser, Jodi; Bontekoe, Emily; Kouta, Ahmed; Farooqui, Ambar; Daravath, Bharathi; et al. (Clinical and applied thrombosis/hemostasis, 2021)
Stevens-Johnson Syndrome (SJS) and toxic epidermal necrolysis (TEN) are Severe Cutaneous Adverse Reactions (SCARS) characterized by fever and mucocutaneous lesions leading to necrosis and sloughing of the epidermis. Conjunctival lesions are reported in 85% of patients. The pathogenesis of SJS/TEN/SCARS is not completely understood. It is hypothesized that IL-13, IL-15 and Granulysin expressed in plasma and skin may play a role. We measured the circulating levels of these cytokines in the plasma using ELISA and their expression in the skin using immunofluorescence microscopy. A total of 12 SJS/TEN skin biopsy samples (8 SJS, 2 SJS/TEN overlap and 2 TEN) were analyzed. Biopsy samples from patients with Lichen Planus (an inflammatory condition of the skin and mucous membranes) served as controls. Studies were also performed in human corneal epithelial cells where expression of these cytokines were measured following a challenge with TNF-α (0, 1, 10 and 100 ng/ml). The intensity of immunofluorescence was measured Using Imaris® software. The results showed significantly increased expression of these cytokines in the skin biopsy samples as measured by the average intensities of IL-13 (6.1 x 133.0 ± 4.231 x 10^8), and Granulysin (4.2 x 123.0 ± 4.231 x 10^8) compared to Lichen planus control (3.0 x 123.0 ±1.62 x 10^5). Increased expression of IL-13 and IL-15 were noted in cell culture studies and in the plasma samples when compared to Normal Human Plasma as controls. It is concluded that IL-13, IL-15 and Granulysin play a role in the pathogenesis of SJS/TEN.